2015
DOI: 10.1097/nen.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Endosomal, Lysosomal, and Autophagic Dysregulation in Mild Cognitive Impairment

Abstract: Endosomal-lysosomal and autophagic dysregulation occurs in the hippocampus in prodromal Alzheimer disease (AD), but its relationship with β-amyloid (Aβ) and tau pathology remain unclear. To investigate this issue, we performed immunoblot analysis of hippocampal homogenates from cases with an antemortem clinical diagnosis of no cognitive impairment, mild cognitive impairment (MCI) and AD. Western blot analysis revealed significant increases in the acid hydrolase cathepsin D (Cat D) and early endosome marker rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 110 publications
4
26
0
Order By: Relevance
“…These results are in line with several observations that endosomal-lysosomal protein trafficking dysfunction is one of the earliest cellular disturbances in AD [37,66,67]. For example, enlarged rab5-positive endosomes occur in pyramidal cells of the neocortex prior to NFT formation [66], and an upregulation of rab5 and cathepsin D in the NBM and hippocampus is observed in MCI compared to NCI [47,53,68]. Whether protein trafficking and degradation facilitate tangle formation or are downstream consequences of tau fibrillization is unclear, but these data strengthen the hypothesis that endosomal-lysosomal abnormalities are an upstream molecular pathogenic event in AD pathophysiology that may be amenable to therapeutic targeting.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with several observations that endosomal-lysosomal protein trafficking dysfunction is one of the earliest cellular disturbances in AD [37,66,67]. For example, enlarged rab5-positive endosomes occur in pyramidal cells of the neocortex prior to NFT formation [66], and an upregulation of rab5 and cathepsin D in the NBM and hippocampus is observed in MCI compared to NCI [47,53,68]. Whether protein trafficking and degradation facilitate tangle formation or are downstream consequences of tau fibrillization is unclear, but these data strengthen the hypothesis that endosomal-lysosomal abnormalities are an upstream molecular pathogenic event in AD pathophysiology that may be amenable to therapeutic targeting.…”
Section: Discussionsupporting
confidence: 88%
“…Custom-designed microarray analysis of single nbM neurons was performed using tissue obtained postmortem from 28 participates in the Rush Religious Orders Study (RROS) (Bennett et al, 2002; Counts et al, 2014; Ginsberg et al, 1997; Mufson et al, 1999) who were clinically diagnosed within a year of death with NCI (n = 10), MCI (n = 10), or mild/moderate AD (n = 8). Details of clinical evaluations and diagnostic criteria in the RROS cohort have been extensively published (Bennett et al, 2002; Counts et al, 2006; Ginsberg et al, 2006; Mufson et al, 1999; Perez et al, 2015a). Briefly, a team of investigators performed an annual clinical examination, including neuropsychological performance testing using the Mini-Mental State Exam (MMSE) and 17 additional neuropsychological tests referable to episodic memory, semantic memory, working memory, perceptual speed, and visuospatial ability.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a team of investigators performed an annual clinical examination, including neuropsychological performance testing using the Mini-Mental State Exam (MMSE) and 17 additional neuropsychological tests referable to episodic memory, semantic memory, working memory, perceptual speed, and visuospatial ability. A Global Cognitive Score (GCS), consisting of a composite z-score calculated from this test battery, was determined for each participant (Bennett et al, 2002; Counts et al, 2006; Ginsberg et al, 2006; Mufson et al, 1999; Perez et al, 2015a). A board-certified neurologist with expertise in the evaluation of the elderly made the clinical diagnosis based on impairments in each of the five cognitive domains and a clinical examination.…”
Section: Methodsmentioning
confidence: 99%
“…Since proteolytic processing of APP is necessary for the formation of Aβ, lysosomal proteases have been linked with AD pathology (Vidoni et al, 2016). The increased expression of cathepsin D reported in this study may represent a compensatory mechanism to restore lysosomal function (Perez et al, 2015). This is supported by another study which showed that knockout of cathepsin D enhances abnormal tau phosphorylation, and oxidative stress in the brain (Khurana et al, 2010).…”
Section: Discussionmentioning
confidence: 87%